The Role of Spatial Gradient on Vertical Total Electron Content Extraction From Geodetic Very Long Baseline Interferometry Observation: Case Study CONT08 to CONT17‐L1 - Hossein Etemadfard; Robert Heinkelmann; Masoud Mashhadi Hossainali; Harald Schuh (Space Weather)
Abstract Geodetic very long baseline interferometry (VLBI) observations are carried out, with the legacy system, using two well‐separated frequency bands in order to determine first‐order ionospheric delay corrections corresponding to the combined effect of total electron content (TEC) at two stations forming a baseline. On the other hand, it is possible to obtain the vertical TEC (VTEC) above the VLBI antennas from VLBI data. This research intends to investigate the role of the ionospheric spatial gradient on VTEC which is derived from VLBI observations based on the latest four Continuous VLBI Campaigns (CONT08 to CONT17‐L1). For this purpose, station‐based VTEC values were computed in two modes, with and without spatial gradients. Then, these two approaches were evaluated by comparison to global ionospheric maps (GIMs). The differences between the GIM‐based VTEC values and the VLBI VTEC values derived using two parameterization approaches were used to compute the Root Mean Square Error (RMSE) for each VLBI station during the CONTs. In addition, the improvement percentages of the VLBI VTEC's error were calculated to understand the spatial gradient role. Based on the obtained results, the role of spatial gradient is more significant on the equatorial region as compared to the polar area. Using the ionospheric spatial gradient decreases the RMSE values of VLBI‐derived VTEC values from CONT08, CONT11, CONT14, and CONT17‐L1 by 26.4%, 37.6%, 32.4%, and 27.4%, respectively. In addition, it is also shown that this parameter reduces the RMSE values during the high solar activity, as in 2011 and 2014.